Influence of Ligand Architecture on Oxidation Reactions by High‐Valent Nonheme Manganese Oxo Complexes Using Water as a Source of Oxygen1. Issue 7 (29th December 2014) - Barman, Prasenjit; Vardhaman, Anil Kumar; Martin, Bodo; Wörner, Svenja J.; Sastri, Chivukula V.; Comba, Peter
Abstract Mononuclear nonheme MnIVO complexes with two isomers of a bispidine ligand have been synthesized and characterized by various spectroscopies and density functional theory (DFT). The MnIVO complexes show reactivity in oxidation reactions (hydrogen‐atom abstraction and sulfoxidation). Interestingly, one of the isomers (L1) is significantly more reactive than the other (L2), while in the corresponding FeIVO based oxidation reactions the L2‐based system was previously found to be more reactive than the L1‐based catalyst. This inversion of reactivities is discussed on the basis of DFT and molecular mechanics (MM) model calculations, which indicate that the order of reactivities are primarily due to a switch of reaction channels (σ versus π) and concomitant steric effects.